A tale of two syn-rifts: New age information and depositional environment interpretation for the North Falkland Basin syn-rift and implications for the rifting of Gondwana - Rory J. Sutton; Gayle E. Plenderleith; Thomas J.H. Dodd; Lorraine P. Field; Ian L. Millar; Dave J. McCarthy; Thomas A. Randles (Gondwana Research, 2026)

Comparing mass balance-based nutrient management planning tools to support crop fertilisation decisions - Octavian P. Chiriac; Zsofia Bakacsi; Béla Pirkó; María-Llanos López; Elena Pareja-Serrano; Gunther Liebhard; Peter Strauss; Barbora Jachymova; Josef Kraza; José A. Gómez; Javier Montoliu; Gema Guzmán; et al. (Nutrient Cycling in Agroecosystems, 2026)
Nutrient management plan (NMP) tools aim to enhance crop production while minimising environmental harm from over-fertilisation by aligning applications with crop demands and with soil and atmospheric conditions. The characteristics of 14 widely used NMP tools from nine countries (Austria, Bulgaria, China, Czech Republic, Hungary, Italy, New Zealand, Spain, and United Kingdom) were compared. All tools employed a mass balance approach at the field and seasonal scales. To evaluate the tools, matrices of the presence/absence of 24 desirable characteristics, 22 nutrient cycle processes and sources, and 38 required input data were compiled. To compare the NMPs, cumulative scores were calculated for each category evaluated. Additionally, two theoretical case studies compared fertiliser recommendations for winter wheat in arable and livestock farming systems. Cluster analysis classified the 14 tools into six clusters, reflecting distinct levels of complexity, usability, adaptability, and interoperability. The number of input data required was strongly and positively correlated with the number of nitrogen (N) processes and sources considered, confirming that input demand reflects tool sophistication. More comprehensive tools tended to recommend lower N application rates in the livestock system, suggesting that simpler tools overestimated N requirements by omitting key processes. However, practical usability characteristics did not determine different recommendations. While N recommendations were broadly aligned with national guidelines, P and K recommendations showed considerably higher variability reflecting the lack of harmonised guidelines for these macronutrients.

Developing a methodology to identify personalities in farmed red deer - B.R. Thompson; D.R. Stevens; I.J. Gordon; T.M.R. Maxwell; S. Zydenbos; K.G. Dodds; D. Triadis; P. Gregorini (Applied Animal Behaviour Science, 2026)

Predictions of southern migration timing in coastal sharks under future ocean warming - Maria H. Manz; Oliver N. Shipley; Robert M. Cerrato; Robert E. Hueter; Alisa L. Newton; John P. Tyminski; Bryan R. Franks; Tobey H. Curtis; Christopher Fischer; Joshua P. Zacharias; Christopher Scott; Keith J. Dunton; et al. (Conservation Biology, 2025)
Projected redistribution of marine species due to ocean warming may undermine current conservation efforts. Yet, there have been few studies on how ocean warming may alter migration timing. Across 5 years of acoustic telemetry data (2018–2022), we determined environmental drivers of southward migration timing for 6 migratory shark species from summer habitats in the Northwest Atlantic Ocean. We then forecasted how migratory timing from 3 regions, between the New England shelf and Mid‐Atlantic Bight, would respond under future sea surface temperatures (SSTs). Photoperiod and SST were strong predictors of southern migration in sharks, but the strength of these effects varied latitudinally. Overall, we found delayed departure dates from summer habitats under future elevated SSTs, indicating prolonged residency in northern habitats (median = ∼12 days). Sandbar sharks ( Carcharhinus plumbeus ) exhibited the largest delay in the onset of southern migrations (median = 29 days), whereas sand tiger sharks ( Carcharias taurus ) and white sharks ( Carcharodon carcharias ) exhibited the smallest delay (median = 1 day). Delays in migration timing of coastal shark species may alter local ecosystem dynamics and challenge current management strategies. These findings illustrate the utility of collaborative data‐sharing networks to expand understanding of broadscale animal movements and contribute to effective species management under a changing climate.

Optimising parent selection in plant breeding: comparing metaheuristic algorithms for genotype building - S. Yadav; S. Dillon; M. McNeil; E. Dinglasan; R. Mago; P. Dodds; L. Hickey; B. J. Hayes (Theoretical and Applied Genetics, 2025)
Stacking desirable haplotypes across the genome to develop superior genotypes has been implemented in several crop species. A major challenge in Optimal Haplotype Selection is identifying a set of parents that collectively contain all desirable haplotypes, a complex combinatorial problem with countless possibilities. In this study, we evaluated the performance of metaheuristic search algorithms (MSAs)—genetic algorithm (GA), differential evolution (DE), particle swarm optimisation (PSO), and simulated annealing (SA) for optimising parent selection under two genotype building (GB) objectives: Optimal Haplotype Selection (OHS) and Optimal Population Value (OPV). Using a diverse wheat population of 583 lines genotyped for 29,972 SNPs, forming 7645 haplotype blocks and phenotyped for stripe rust scores, we assessed each algorithm’s performance across fitness optimisation, convergence speed, and computational efficiency. GA consistently achieved high fitness and rapid convergence, while DE showed robustness but required longer runtime and careful tuning. PSO performed well under the OHS criterion but was less effective for OPV. SA, although computationally lighter, was less consistent in finding optimal solutions. Simulation over 100 breeding cycles showed that OHS outperformed both OPV and GEBV-based selection in long-term genetic gain and diversity retention. OHS maintained heterozygosity and additive variance, which are key for sustainable improvement, while GEBV selection led to early allele fixation. Our findings underscore the potential of GB strategies that prioritise the collective performance of parent sets rather than individual ranking to enhance selection outcomes in genomic-assisted breeding programmes.

Correction to: A global review of white shark (Carcharodon carcharias) parturition - Craig P. O’Connell; Jon F. Dodd; Julia Crews; Juliet Gressle; Breanna Racicot; Steven Sitzer; Timothy Lis; Gregory B. Skomal (Reviews in Fish Biology and Fisheries, 2025)

Spatial ecology and population dynamics of brown trout Salmo trutta L. in reservoirs and headwater tributaries - Jamie R. Dodd; Richard A. A. Noble; Andy D. Nunn; Holly M. Owen; Paolo Moccetti; Jonathan P. Harvey; Liam Wallace; Ben Gillespie; Domino A. Joyce; Jonathan D. Bolland (Journal of Fish Biology, 2025)
This investigation compared the spatial ecology and population dynamics of brown trout Salmo trutta L. between reservoirs with (impact; Langsett Reservoir) and without (control; Grimwith Reservoir) barriers to fish movements into headwater tributaries, and the effectiveness of a fish pass intended to remediate connectivity. Passive integrated transponder (PIT) telemetry revealed that fish that emigrated from Langsett and Grimwith tributaries were 1–3 and 0–2 years old, respectively, and predominantly did so in spring and autumn‐early winter in both systems. Weirs at Langsett Reservoir appeared to thwart emigration rate (26%) relative to Grimwith Reservoir (85%). Acoustic telemetry (two‐dimensional positions) in the impacted reservoir revealed that the largest home range was in October–December (95% monthly activity space S.D. up to 26.9 ± 6.69 ha in November), activity was influenced by both month and time of day, and fish occupied shallow water depths (relative to reservoir depth), especially at night. Brown trout tagged in Grimwith and Langsett Reservoirs (42.9% and 64.1%, respectively) and fish tagged in the tributaries that emigrated (37.2% and 27.7%, respectively) were detected immigrating into tributaries throughout the year. At both reservoirs, peak immigration for ≥3‐year‐old trout occurred primarily in autumn‐early winter. Overall passage efficiency went from 3% prior to remediation to 14% after and there was no significant increase in fish densities following the construction of the fish pass. Fish were attracted towards and entered the fish pass under a wide range of river levels, but only succeeded in passing upstream during low levels, which are uncommon druing the main migration period. Overall, this investigation significantly furthers our understanding of brown trout spatial ecology and population dynamics in reservoirs and headwater tributaries.

A global review of white shark (Carcharodon carcharias) parturition - Craig P. O’Connell; Jon F. Dodd; Julia Crews; Juliet Gressle; Breanna Racicot; Steven Sitzer; Timothy Lis; Gregory B. Skomal (Reviews in Fish Biology and Fisheries, 2024)

Construction of relatedness matrices in autopolyploid populations using low-depth high-throughput sequencing data - Timothy P. Bilton; Sanjeev Kumar Sharma; Matthew R. Schofield; Michael A. Black; Jeanne M. E. Jacobs; Glenn J. Bryan; Ken G. Dodds (Theoretical and Applied Genetics, 2024)
Key message An improved estimator of genomic relatedness using low-depth high-throughput sequencing data for autopolyploids is developed. Its outputs strongly correlate with SNP array-based estimates and are available in the package GUSrelate. Abstract High-throughput sequencing (HTS) methods have reduced sequencing costs and resources compared to array-based tools, facilitating the investigation of many non-model polyploid species. One important quantity that can be computed from HTS data is the genetic relatedness between all individuals in a population. However, HTS data are often messy, with multiple sources of errors (i.e. sequencing errors or missing parental alleles) which, if not accounted for, can lead to bias in genomic relatedness estimates. We derive a new estimator for constructing a genomic relationship matrix (GRM) from HTS data for autopolyploid species that accounts for errors associated with low sequencing depths, implemented in the R package GUSrelate. Simulations revealed that GUSrelate performed similarly to existing GRM methods at high depth but reduced bias in self-relatedness estimates when the sequencing depth was low. Using a panel consisting of 351 tetraploid potato genotypes, we found that GUSrelate produced GRMs from genotyping-by-sequencing (GBS) data that were highly correlated with a GRM computed from SNP array data, and less biased than existing methods when benchmarking against the array-based GRM estimates. GUSrelate provides researchers with a tool to reliably construct GRMs from low-depth HTS data.

Dose addition in mixtures of compounds with dissimilar endocrine modes of action in in vitro receptor activation assays and the zebrafish sexual development test - Toine FH. Bovee; Harm J. Heusinkveld; Sophie Dodd; Ad Peijnenburg; Deborah Rijkers; Marco Blokland; R Corinne Sprong; Amélie Crépet; Antsje Nolles; Edwin P. Zwart; Eric R. Gremmer; Leo TM van der Ven (Food and Chemical Toxicology, 2024)

Hydrogen isotope biogeochemistry of plant waxes in paired lake catchments - Mariliis Eensalu; Daniel B. Nelson; Anna Buczynska; Oliver Rach; Eric S. Klein; Justin P. Dodd; Anneli Poska; Nathan D. Stansell (Organic Geochemistry, 2023)

Nutrient and stoichiometric time series measurements of decomposing coarse detritus in freshwaters - Caleb J. Robbins; Beth C. Norman; Halvor M. Halvorson; David W. P. Manning; Elliot Bastias; Cristiane Biasi; Allyn K. Dodd; Rebecca A. Eckert; Alice Gossiaux; Jérémy Jabiol; Andrew S. Mehring; Ada Pastor (Ecology, 2023)
Decomposition of coarse detritus (e.g., dead organic matter larger than ~1 mm such as leaf litter or animal carcasses) in freshwater ecosystems is well described in terms of mass loss, particularly as rates that compress mass loss into one number (e.g., a first‐order decay coefficient, or breakdown rate, “ k ”); less described are temporal changes in the elemental composition of these materials during decomposition, with important implications for elemental cycling from microbes to ecosystems. This stands in contrast with work in the terrestrial realm, where a focus on detrital elemental cycling has provided a sharper mechanistic understanding of decomposition, especially with specific processes such as immobilization and mineralization. Notably, freshwater ecologists often measure carbon (C), nitrogen (N), and phosphorus (P), and their stoichiometric ratios in decomposing coarse materials, including carcasses, wood, leaf litter, and more, but these measurements remain piecemeal. These detrital nutrients are measurements of the entire detrital–microbial complex and are integrative of numerous processes, especially nutrient immobilization and mineralization, and associated microbial growth and death. Thus, data relevant to an elemental, mechanistically focused decomposition ecology are available in freshwaters, but have not been fully applied to that purpose. We synthesized published detrital nutrient and stoichiometry measurements at a global scale, yielding 4038 observations comprising 810 decomposition time series (i.e., measurements within a defined cohort of decomposing material through time) to build a basis for understanding the temporality of elemental content in freshwater detritus. Specifically, the dataset focuses on temporally and ontogenetically (mass loss) explicit measurements of N, P, and stoichiometry (C:N, C:P, N:P). We also collected ancillary data, including detrital characteristics (e.g., species, lignin content), water physiochemistry, geographic location, incubation system type, and methodological variables (e.g., bag mesh size). These measurements are important to unlocking mechanistic insights into detrital ontogeny (the temporal trajectory of decomposing materials) that can provide a deeper understanding of heterotroph‐driven C and nutrient cycling in freshwaters. Moreover, these data can help to bridge aquatic and terrestrial decomposition ecology, across plant or animal origin. By focusing on temporal trajectories of elements, this dataset facilitates cross‐ecosystem comparisons of fundamental decomposition controls on elemental fluxes. It provides a strong starting point (e.g., via modeling efforts) for comparing processes such as immobilization and mineralization that are understudied in freshwaters. Time series from decomposing leaf litter, particularly in streams, are common in the dataset, but we also synthesized ontogenies of animal‐based detritus, which tend to decompose rapidly compared with plant‐based detritus that contains high concentrations of structural compounds such as lignin and cellulose. Although animal‐based data were rare, comprising only three time series, their inclusion in this dataset underscores the opportunities to develop an understanding of decomposition that encompasses all detrital types, from carrion to leaf litter. There are no copyright or proprietary restrictions on the dataset; please cite this data paper when reusing these materials.

Nutrient and stoichiometry dynamics of decomposing litter in stream ecosystems: A global synthesis - Caleb J. Robbins; David W. P. Manning; Halvor M. Halvorson; Beth C. Norman; Rebecca A. Eckert; Ada Pastor; Allyn K. Dodd; Jérémy Jabiol; Elliot Bastias; Alice Gossiaux; Andrew S. Mehring (Ecology, 2023)
Decomposing organic matter forms a substantial resource base, fueling the biogeochemical function and secondary production of most aquatic ecosystems. However, detrital N (nitrogen) and P (phosphorus) dynamics remain relatively unexplored in aquatic ecosystems relative to terrestrial ecosystems, despite fundamentally linking microbial processes to ecosystem function across broad spatial scales. We synthesized 217 published time series of detrital carbon (C), N, P, and their stoichiometric ratios (C:N, C:P, N:P) from stream ecosystems to analyze the temporal nutrient dynamics of decomposing litter using generalized additive models. Model results indicated that detritus was a net source of N (irrespective of inorganic or organic form) to the environment, regardless of initial N content. In contrast, P sink/source dynamics were more strongly influenced by the initial P content, in which P‐poor litters were sinks for nutrients until these shifted to net P mineralization after ~40% mass loss. However, large variations surrounded both the N and P predictions, suggesting the importance of nonmicrobial factors such as fragmentation by invertebrates. Detrital C:N ratios converged and became more similar toward the end of the decomposition, suggesting predictable microbial functional effects throughout detrital ontogeny. C:P and N:P ratios also converged to some degree, but these model predictions were less robust than for C:N, due in part to the lower number of published detrital C:P time series. The explorations of environmental covariate effects were frequently limited by a few coincident covariate measurements across studies, but temperature, N availability, and P tended to accelerate the existing ontogenetic patterns in C:N. Our analysis helps to unite organic matter decomposition across aquatic–terrestrial boundaries by describing the basic patterns of elemental flows catalyzed by decomposition in streams, and points to a research agenda with which to continue addressing gaps in our knowledge of detrital nutrient dynamics across ecosystems.

Water mass composition in Fram Strait determined from the combination of 129I and 236U: Changes between 2016, 2018, and 2019 - A.-M. Wefing; N. Casacuberta; M. Christl; P. A. Dodd (Frontiers in Marine Science, 2022)
Changes in the provenance and composition of waters exported from the Arctic Ocean have the potential to impact large-scale ocean circulation processes in the sub-polar North Atlantic. The main conveyor of waters from the Arctic Ocean to lower latitudes is the East Greenland Current (EGC), flowing southward through Fram Strait. It is therefore crucial to determine and monitor the composition of the EGC, a mixture of polar waters of different origins. Here we present a pilot study on the potential of the long-lived anthropogenic radionuclides 129 I and 236 U as tracers of the EGC water mass composition, based on a time series of 236 U and 129 I concentrations measured across Fram Strait in the years 2016, 2018, and 2019. The overall spatial distribution of 236 U and 129 I was similar among the three sampling years, but a decrease in concentration was observed in the upper water column of the EGC. The observed changes could only partly be attributed to the transient nature of the radionuclide signals, but instead pointed to changes in the EGC water mass composition. To investigate these changes, 236 U and 129 I were first combined in a mixing model featuring the endmembers expected in the upper EGC. We distinguished between Pacific Water (PAC), Atlantic Water advected from the Arctic Ocean (ATL), and Atlantic Water recirculating in Fram Strait (RAC). In 236 U- 129 I tracer space, PAC and RAC showed similar tracer signatures, but were well distinguished from ATL. From 2016 to 2018/19, a decrease in the ATL fraction was evident for the upper EGC. Secondly, the respective combination of 236 U and 129 I with salinity showed differences in absolute water mass fractions, but similar temporal trends. Both suggested an increase in PAC of about 20% for the uppermost layer of the EGC (samples with potential densities below 26.5) and an increase in RAC of about 10−20 % for denser samples. 129 I and 236 U, in combination with salinity, were shown to be suitable tracers to investigate water mass composition in Fram Strait, with the advantage that they can distinguish Atlantic Water advected from the Arctic Ocean from that recirculating in Fram Strait.

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Tidal Marsh Restoration Optimism in a Changing Climate and Urbanizing Seascape - Nathan J. Waltham; Caitlin Alcott; Myriam A. Barbeau; Just Cebrian; Rod M. Connolly; Linda A. Deegan; Kate Dodds; Lucy A. Goodridge Gaines; Ben L. Gilby; Christopher J. Henderson; Catherine M. McLuckie; Thomas J. Minello; et al. (Estuaries and Coasts, 2021)

Preparing interdisciplinary leadership for a sustainable future - Christopher G. Boone; Steward T. A. Pickett; Gabriele Bammer; Kamal Bawa; Jennifer A. Dunne; Iain J. Gordon; David Hart; Jessica Hellmann; Alison Miller; Mark New; Jean P. Ometto; Ken Taylor; et al. (Sustainability Science, 2020)

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Nanogeochemistry of hydrothermal magnetite - Artur P. Deditius; Martin Reich; Adam C. Simon; Alexandra Suvorova; Jaayke Knipping; Malcolm P. Roberts; Sergey Rubanov; Aaron Dodd; Martin Saunders (Contributions to Mineralogy and Petrology, 2018)

The influence of aquaculture unit proximity on the pattern of Lepeophtheirus salmonis infection of anadromous Salmo trutta populations on the isle of Skye, Scotland - I. Moore; J. A. Dodd; M. Newton; C. W. Bean; I. Lindsay; P. Jarosz; C. E. Adams (Journal of Fish Biology, 2018)
A total of 230 anadromous Salmo trutta (brown trout) were sampled in five sheltered coastal fjords (or sea lochs) on the Isle of Skye, Scotland, U.K., in 2016 at varying distances from active Atlantic salmon Salmo salar farms. Statistical models were developed to investigate potential correlations between salmon lice Lepeophtheirus salmonis burdens on S. trutta hosts and their proximity to S. salar farm cages. Significant correlations were found between lice burdens and fish fork length and proximity to the nearest S. salar farm. The probability of the presence of L. salmonis on fish hosts increased with fish host size and with distance from the nearest S. salar farm, but total lice burdens were highest in fish sampled near S. salar farms and decreased with distance. The proportion of different life‐cycle stages of L. salmonis were also dependent on S. salar farm proximity, with higher juvenile lice numbers recorded at sites near S. salar farm cages. These results highlight the complexity of the relationship between S. trutta and L. salmonis infections on wild fish and emphasize the requirement of further research to quantify these effects to better inform conservation and management strategies, particularly in areas of active S. salar farm facilities.

The impact of a small-scale riverine obstacle on the upstream migration of Atlantic Salmon - M. Newton; J. A. Dodd; J. Barry; P. Boylan; C. E. Adams (Hydrobiologia, 2018)

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

Methods to estimate changes in soil water for phenotyping root activity in the field - W.R. Whalley; A. Binley; C.W. Watts; P. Shanahan; I.C. Dodd; E.S. Ober; R.W. Ashton; C.P. Webster; R.P. White; M. J. Hawkesford (Plant and Soil, 2017)

Transitions in climate and energy discourse between Hurricanes Katrina and Sandy - Emily M. Cody; Jennie C. Stephens; James P. Bagrow; Peter Sheridan Dodds; Christopher M. Danforth (Journal of Environmental Studies and Sciences, 2017)

Spatial and temporal constraints on regional-scale groundwater flow in the Pampa del Tamarugal Basin, Atacama Desert, Chile - Richard S. Jayne; Ryan M. Pollyea; Justin P. Dodd; Elizabeth J. Olson; Susan K. Swanson (Hydrogeology Journal, 2016)

Spatial and successional dynamics of microbial biofilm communities in a grassland stream ecosystem - Allison M. Veach; James C. Stegen; Shawn P. Brown; Walter K. Dodds; Ari Jumpponen (Molecular Ecology, 2016)
Biofilms represent a metabolically active and structurally complex component of freshwater ecosystems. Ephemeral prairie streams are hydrologically harsh and prone to frequent perturbation. Elucidating both functional and structural community changes over time within prairie streams provides a general understanding of microbial responses to environmental disturbance. We examined microbial succession of biofilm communities at three sites in a third‐order stream at Konza Prairie over a 2‐ to 64‐day period. Microbial abundance (bacterial abundance, chlorophyll a concentrations) increased and never plateaued during the experiment. Net primary productivity (net balance of oxygen consumption and production) of the developing biofilms did not differ statistically from zero until 64 days suggesting a balance of the use of autochthonous and allochthonous energy sources until late succession. Bacterial communities (MiSeq analyses of the V4 region of 16S rRNA) established quickly. Bacterial richness, diversity and evenness were high after 2 days and increased over time. Several dominant bacterial phyla (Beta‐, Alphaproteobacteria, Bacteroidetes, Gemmatimonadetes, Acidobacteria, Chloroflexi) and genera ( Luteolibacter , Flavobacterium , Gemmatimonas , Hydrogenophaga ) differed in relative abundance over space and time. Bacterial community composition differed across both space and successional time. Pairwise comparisons of phylogenetic turnover in bacterial community composition indicated that early‐stage succession (≤16 days) was driven by stochastic processes, whereas later stages were driven by deterministic selection regardless of site. Our data suggest that microbial biofilms predictably develop both functionally and structurally indicating distinct successional trajectories of bacterial communities in this ecosystem.

Does size matter? A test of size‐specific mortality in Atlantic salmon Salmo salar smolts tagged with acoustic transmitters - M. Newton; J. Barry; J. A. Dodd; M. C. Lucas; P. Boylan; C. E. Adams (Journal of Fish Biology, 2016)
Mortality rates of wild Atlantic salmon Salmo salar smolts implanted with acoustic transmitters were assessed to determine if mortality was size dependent. The routinely accepted, but widely debated, ‘2% transmitter mass: body mass’ rule in biotelemetry was tested by extending the transmitter burden up to 12·7% of body mass in small [mean fork length ( L F ) 138·3 mm, range 115–168 mm] downstream migrating S. salar smolts. Over the short timescale of emigration (range 11·9–44·5 days) through the lower river and estuary, mortality was not related to S. salar size, nor was a relationship found between mortality probability and transmitter mass: body mass or transmitter length: L F ratios. This study provides further evidence that smolt migration studies can deviate from the ‘2% rule’ of thumb, to more appropriate study‐specific measures, which enables the use of fishes representative of the body size in natural populations without undue effects.

Lake bathymetry and species occurrence predict the distribution of a lacustrine apex predator - M. R. Hughes; J. A. Dodd; P. S. Maitland; C. E. Adams (Journal of Fish Biology, 2016)
This study examined the abiotic and biotic characteristics of ecosystems that allow expression of a life history called ferox trout, the colloquial name given to brown trout Salmo trutta adopting a piscivorous life history strategy, an apex predator in post‐glacial lakes in northern Europe. One hundred and ninety‐two lakes in Scotland show evidence of currently, or historically, supporting ferox S. trutta ; their presence was predicted in logistic models by larger and deeper lakes with a large catchment that also support populations of Arctic charr Salvelinus alpinus .

Foraging specialisms influence space use and movement patterns of the European eel Anguilla anguilla - J. Barry; M. Newton; J. A. Dodd; O. E. Hooker; P. Boylan; M. C. Lucas; C. E. Adams (Hydrobiologia, 2016)

Freshwater and coastal migration patterns in the silver‐stage eel Anguilla anguilla - J. Barry; M. Newton; J. A. Dodd; M. C. Lucas; P. Boylan; C. E. Adams (Journal of Fish Biology, 2016)
The unimpeded downstream movement patterns and migration success of small female and male Anguilla anguilla through a catchment in north‐west Europe were studied using an acoustic hydrophone array along the River Finn and into the Foyle Estuary in Ireland. Twenty silver‐stage A. anguilla (total length, L T , range: 332–520 mm) were trapped 152 km upstream from a coastal marine sea‐lough outlet and internally tagged with acoustic transmitters of which 19 initiated downstream migration. Migration speed was highly influenced by river flow within the freshwater ( FW ) compartment. Anguilla anguilla activity patterns were correlated with environmental influences; light, tidal direction and lunar phase all influenced the initiation of migration of tagged individuals. Migration speed varied significantly between upstream and lower river compartments. Individuals migrated at a slower speed in transitional water and sea‐lough compartments compared with the FW compartment. While 88·5% survival was recorded during migration through the upper 121 km of the river and estuary, only 26% of A. anguilla which initiated downstream migration were detected at the outermost end of the acoustic array. Telemetry equipment functioned efficiently, including in the sea‐lough, so this suggests high levels of mortality during sea‐lough migration, or less likely, long‐term sea‐lough residence by silver A. anguilla emigrants. This has important implications for eel management plans.

The effect of impedance to root growth on plant architecture in wheat - Kemo Jin; Jianbo Shen; Rhys W. Ashton; Rodger P. White; Ian C. Dodd; Andrew L. Phillips; Martin A. J. Parry; William R. Whalley (Plant and Soil, 2015)

Wheat root growth responses to horizontal stratification of fertiliser in a water-limited environment - Kemo Jin; Jianbo Shen; Rhys W. Ashton; Rodger P. White; Ian C. Dodd; Martin A. J. Parry; William R. Whalley (Plant and Soil, 2015)

Introduced parasite Anguillicola crassus infection significantly impedes swim bladder function in the European eel Anguilla anguilla (L.) - J Barry; J McLeish; J A Dodd; J F Turnbull; P Boylan; C E Adams (Journal of Fish Diseases, 2014)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Factors affecting the foraging behaviour of the European shag: implications for seabird tracking studies - L. M. Soanes; J. P. Y. Arnould; S. G. Dodd; G. Milligan; J. A. Green (Marine Biology, 2014)

A standardised protocol for the validation of banking methodologies for arterial allografts - R. J. Lomas; P. D. F. Dodd; P. Rooney; D. E. Pegg; P. A. Hogg; M. E. Eagle; K. E. Bennett; A. Clarkson; J. N. Kearney (Cell and Tissue Banking, 2013)

Genotypic variation in the ability of wheat roots to penetrate wax layers - W. R. Whalley; I. C. Dodd; C. W. Watts; C. P. Webster; A. L. Phillips; J. Andralojc; R. P. White; W. J. Davies; M. A. J. Parry (Plant and Soil, 2013)

Liquid export of Arctic freshwater components through the Fram Strait 1998–2011 - B. Rabe; P. A. Dodd; E. Hansen; E. Falck; U. Schauer; A. Mackensen; A. Beszczynska-Möller; G. Kattner; E. J. Rohling; K. Cox (Ocean Science, 2013)
We estimated the magnitude and composition of southward liquid freshwater transports in the East Greenland Current near 79° N in the Western Fram Strait between 1998 and 2011. Previous studies have found this region to be an important pathway for liquid freshwater export from the Arctic Ocean to the Nordic Seas and the North Atlantic subpolar gyre. Our transport estimates are based on six hydrographic surveys between June and September and concurrent data from moored current meters. We combined concentrations of liquid freshwater, meteoric water (river water and precipitation), sea ice melt and brine from sea ice formation, and Pacific Water, presented in Dodd et al. (2012), with volume transport estimates from an inverse model. The average of the monthly snapshots of southward liquid freshwater transports between 10.6° W and 4° E is 100 ± 23 mSv (3160 ± 730 km3 yr−1), relative to a salinity of 34.9. This liquid freshwater transport consists of about 130% water from rivers and precipitation (meteoric water), 30% freshwater from the Pacific, and −60% (freshwater deficit) due to a mixture of sea ice melt and brine from sea ice formation. Pacific Water transports showed the highest variation in time, effectively vanishing in some of the surveys. Comparison of our results to the literature indicates that this was due to atmospherically driven variability in the advection of Pacific Water along different pathways through the Arctic Ocean. Variations in most liquid freshwater component transports appear to have been most strongly influenced by changes in the advection of these water masses to the Fram Strait. However, the local dynamics represented by the volume transports influenced the liquid freshwater component transports in individual years, in particular those of sea ice melt and brine from sea ice formation. Our results show a similar ratio of the transports of meteoric water and net sea ice melt as previous studies. However, we observed a significant increase in this ratio between the surveys in 1998 and in 2009. This can be attributed to higher concentrations of sea ice melt in 2009 that may have been due to enhanced advection of freshwater from the Beaufort Gyre to the Fram Strait. Known trends and variability in the Arctic liquid freshwater inflow from rivers are not likely to have had a significant influence on the variation of liquid freshwater component transports between our surveys. On the other hand, known freshwater inflow variability from the Pacific could have caused some of the variation we observed in the Fram Strait. The apparent absence of a trend in southward liquid freshwater transports through the Fram Strait and recent evidence of an increase in liquid freshwater storage in the Arctic Ocean raise the question: how fast will the accumulated liquid freshwater be exported from the Arctic Ocean to the deep water formation regions in the North Atlantic and will an increased export occur through the Fram Strait.

Disease-Driven Amphibian Declines Alter Ecosystem Processes in a Tropical Stream - M. R. Whiles; R. O. Hall; W. K. Dodds; P. Verburg; A. D. Huryn; C. M. Pringle; K. R. Lips; S. S. Kilham; C. Colón-Gaud; A. T. Rugenski; S. Peterson; S. Connelly (Ecosystems, 2013)

Effects of mu opioid receptor antagonism on cognition in obese binge-eating individuals - Samuel R. Chamberlain; Karin Mogg; Brendan P. Bradley; Annelize Koch; Chris M. Dodds; Wenli X. Tao; Kay Maltby; Bhopinder Sarai; Antonella Napolitano; Duncan B. Richards; Edward T. Bullmore; Pradeep J. Nathan (Psychopharmacology, 2012)

How can soil monitoring networks be used to improve predictions of organic carbon pool dynamics and CO2 fluxes in agricultural soils? - Bas van Wesemael; Keith Paustian; Olof Andrén; Carlos E. P. Cerri; Mike Dodd; Jorge Etchevers; Esther Goidts; Peter Grace; Thomas Kätterer; Brian G. McConkey; Stephen Ogle; Genxing Pan; et al. (Plant and Soil, 2011)

Genetic analysis of physiological components of salt tolerance conferred by Solanum rootstocks. What is the rootstock doing for the scion? - M. J. Asins; M. C. Bolarín; F. Pérez-Alfocea; M. T. Estañ; C. Martínez-Andújar; A. Albacete; I. Villalta; G. P. Bernet; Ian C. Dodd; E. A. Carbonell (Theoretical and Applied Genetics, 2010)

Dye-tracing studies in southwestern Missouri, USA: indication of stratigraphic flow control in the Burlington Limestone - Douglas Gouzie; Rebecca P. Dodd; David M. White (Hydrogeology Journal, 2010)

What tissue bankers should know about the use of allograft blood vessels - P. Dominic F. Dodd (Cell and Tissue Banking, 2010)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Late Holocene storm-trajectory changes inferred from the oxygen isotope composition of lake diatoms, south Alaska - Caleb J. Schiff; Darrell S. Kaufman; Alexander P. Wolfe; Justin Dodd; Zachary Sharp (Journal of Paleolimnology, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The galactophilic lectin, LecA, contributes to biofilm development in Pseudomonas aeruginosa - Stephen P. Diggle; Rachael E. Stacey; Christine Dodd; Miguel Cámara; Paul Williams; Klaus Winzer (Environmental Microbiology, 2006)
Summary LecA (PA‐IL) is a cytotoxic lectin and adhesin produced by Pseudomonas aeruginosa which binds hydrophobic galactosides with high specificity and affinity. By using a lecA–egfp translation fusion and immunoblot analysis of the biofilm extracellular matrix, we show that lecA is expressed in biofilm‐grown cells. In static biofilm assays on both polystyrene and stainless steel, biofilm depth and surface coverage was reduced by mutation of lecA and enhanced in the LecA‐overproducing strain PAO‐P47. Biofilm surface coverage by the parent strain, PAO‐P47 but not the lecA mutant on steel coupons was also inhibited by growth in the presence of either isopropyl‐β‐D‐thiogalactoside (IPTG) or p ‐nitrophenyl‐α‐D‐galactoside (NPG). Furthermore, mature wild‐type biofilms formed in the absence of these hydrophobic galactosides could be dispersed by the addition of IPTG. In contrast, addition of p ‐nitrophenyl‐α‐L‐fucose (NPF) which has a high affinity for the P. aeruginosa LecB (PA‐IIL) lectin had no effect on biofilm formation or dispersal. Planktonic growth of P. aeruginosa PAO1 was unaffected by the presence of IPTG, NPG or NPF, nor was the strain able to utilize these sugars as carbon sources, suggesting that the observed effects on biofilm formation were due to the competitive inhibition of LecA–ligand binding. Similar results were also obtained for biofilms grown under dynamic flow conditions on steel coupons, suggesting that LecA contributes to P. aeruginosa biofilm architecture under different environmental conditions.

Studies on the diversity of arbuscular mycorrhizal fungi and the efficacy of two native isolates in a highly alkaline anthropogenic sediment - R. S. Oliveira; M. Vosátka; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2005)

Differential expression of the GABA transporters GAT-1 and GAT-3 in brains of rats, cats, monkeys and humans - David V. Pow; Robert K. P. Sullivan; Susan M. Williams; Heather L. Scott; Peter R. Dodd; David Finkelstein (Cell and Tissue Research, 2005)

The effects of phosphorus nutrition and soil pH on the growth of some ancient woodland indicator plants and their interaction with competitor species - N. A. Hipps; M. J. Davies; P. Dodds; G. P. Buckley (Plant and Soil, 2005)

Studies on the diversity of the distinct phylogenetic lineage encompassing Glomus claroideum and Glomus etunicatum - Alia Rodriguez; Justin P. Clapp; Louisa Robinson; John C. Dodd (Mycorrhiza, 2005)

The role of arbuscular mycorrhizal fungi in plant community establishment at Samphire Hoe, Kent, UK – the reclamation platform created during the building of the Channel tunnel between France and UK - John C. Dodd; Tim A Dougall; Justin P. Clapp; Peter Jeffries (Biodiversity and Conservation, 2002)

Ribotyping of rhizobia nodulating Acacia mangium and Paraserianthes falcataria from different geographical areas in Indonesia using PCR‐RFLP‐SSCP (PRS) and sequencing - Justin P. Clapp; Irdika Mansur; John C. Dodd; Peter Jeffries (Environmental Microbiology, 2001)
Acacia mangium and Paraserianthes falcataria are leguminous tree species widely grown for timber in Indonesia and other tropical countries, yet little is known about the identity of their rhizobial symbionts. Polymerase chain reaction‐restriction fragment length polymorphism‐single‐strand conformational polymorphism (PRS) analysis of the 16S rRNA gene was used along with sequencing to assess the diversity of 57 rhizobia isolated from nodules of A. mangium and P. falctaria in Indonesia. In total, 26 rhizobia isolated from A. mangium were analysed by PRS and sequencing. The PRS patterns indicated that 12 (46%) clustered with Bradyrhizobium elkanii , 13 (50%) with B. lianoningense / japonicum and one (4%) with Mesorhizobium loti . Thirty‐one isolates were analysed from P. falcataria : five (16%) clustered with B. elkanii and 26 (84%) with B. lianoningense / japonicum. These results were confirmed by phylogenetic analysis of sequences. Intraspecific diversity of the 16S rRNA genes from rhizobia nodulating A. mangium and P. falcataria revealed by PRS was low, only one genotype was found within the isolates that clustered with B. elkanii and two within the B. liaoningense / japonicum group. These Bradyrhizobium species are apparently ubiquitous throughout the Indonesian archipelago and it is clear why the two tree species are able to successfully establish outside their native range without the need for inoculation with indigenous rhizobia.

The mycorrhizal status of Phragmites australis in several polluted soils and sediments of an industrialised region of Northern Portugal - R.S. Oliveira; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2001)

A genetic map of the Nicotiana alata S locus that includes three pollen-expressed genes - J.-H. Li; N. Nass; M. Kusaba; P. N. Dodds; N. Treloar; A. E. Clarke; E. Newbigin (Theoretical and Applied Genetics, 2000)

A second-generation linkage map of the sheep genome - Maurico J. de Gortari; Brad A. Freking; Rachel P. Cuthbertson; Steven M. Kappes; John W. Keele; Roger T. Stone; Kreg A. Leymaster; Ken G. Dodds; Allan M. Crawford; Craig W. Beattie (Mammalian Genome, 1998)

Protein engineering of lantibiotics - Oscar P. Kuipers; Gabriele Bierbaum; Birgit Ottenwälder; Helen M. Dodd; Nicky Horn; Jörg Metzger; Thomas Kupke; Volker Gnau; Roger Bongers; Patrick van den Bogaard; Hans Kosters; Harry S. Rollema; et al. (Antonie van Leeuwenhoek, 1996)